Diseño y construcción de un fermentador aerobio de café con control de temperatura - Robles Granda, Alex Vicente (2023)
This work contemplates the design, construction and evaluation of an aerobic coffee fermenter with temperature control to improve the fermentation process in the wet benefit. First, similar or analogous machines such as dough and powder mixers are identified to recognize the mechanisms and parts that make them up, in addition to recognizing how they work, then the shape of the tank, type of mixer, cooling/heating system and control system to be designed are selected, taking into account maneuverability, mixing time and variables to control in the fermenter such as time and temperature. As for the materials, those available in the local market are used; stainless steel is required for the tank, while galvanized steel is required for the structure because it works with fluids and seeks to avoid the appearance of rust, in the water recirculation system a level hose, check valves and solenoid valves are used, while the control system is mainly made up of relays and a temperature controller, the systems were designed taking into account their future maintenance and validating their parts. Finally, to carry out the performance tests, 22 lb of pulped coffee are used, three performance tests were carried out with a time of 14 hours at different temperatures, the coffee was purchased from the city of Alamor, obtaining very good results in terms of the precision of the control of the fermentation temperature in the coffee during the 14 hours, verifying that the machine works correctly. Keywords: design, construction, machine, fermenter, temperature, time, coffee.